Pemphigus Vulgaris Confined to the Gingiva: A Case Report - Ohta, Mitsuhiro (Hindawi Publishing Corporation, 2011)
Pemphigus Vulgaris (PV) is an autoimmune intraepithelial blistering disease involving the skin and mucous membranes. Oral mucosa is frequently affected in patients with PV, and oral lesions may be the first sign of the disease in majority of patients. In some patients, oral lesions may also be followed by skin involvement. Therefore, timely recognition and therapy of oral lesions is critical as it may prevent skin involvement. Early oral lesions of PV are, however, often regarded as difficult to diagnose, since the initial oral lesions may be relatively nonspecific, manifesting as superficial erosions or ulcerations, and rarely presenting with the formation of intact bullae. Lesions may occur anywhere on the oral mucosa including gingiva; however; desquamtive gingivitis is less common with PV than other mucocutaneous conditions such as pemphigoid or lichen planus. This paper describes the case of a patient presenting with a one-year history of painful gingival, who is finally diagnosed as having PV.